2019
DOI: 10.1111/ecc.12991
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted biographies and balancing identities: A qualitative study of cancer patients’ communication with healthcare professionals about dependent children

Abstract: Objective About 14% of cancer patients live with dependent children. Healthcare professionals are well placed to help patients support their children as part of a patient‐centred practice. Children tend to appreciate open communication during the course of illness, but patients often find this difficult. However, research is unclear about patients’ preferences and their willingness to talk with healthcare professionals about their dependent children. Methods We conducted 15 in‐depth interviews with patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…We also found it was common for HPs to have limited knowledge and experience with children and this was likely to affect their confidence to approach patients' children or have conversations with patients about their children. This supports earlier studies that found staff are encumbered by their lack of knowledge and expertise regarding children (Dencker et al, 2019;Grant, Sangha, Lister, & Wiseman, 2016;Turner et al, 2009) and require more education and experience to improve their confidence in supporting patients'…”
Section: Parents Want To Protect Their Childrensupporting
confidence: 89%
See 4 more Smart Citations
“…We also found it was common for HPs to have limited knowledge and experience with children and this was likely to affect their confidence to approach patients' children or have conversations with patients about their children. This supports earlier studies that found staff are encumbered by their lack of knowledge and expertise regarding children (Dencker et al, 2019;Grant, Sangha, Lister, & Wiseman, 2016;Turner et al, 2009) and require more education and experience to improve their confidence in supporting patients'…”
Section: Parents Want To Protect Their Childrensupporting
confidence: 89%
“…Patients wait for their oncologist or other team member to instigate discussion (Dencker et al, 2019), and children do not recognise hospitals as a place to seek emotional support (Finch & Gibson, 2009).…”
Section: Health Professionalsmentioning
confidence: 99%
See 3 more Smart Citations